Benefits due public school teachers under section 699 of the revised administrative code, as amended by Republic Act. no. 1232 - Hernandez, Honorata Pangan 1928- ([Quezon City s.n.], 1973)
This study analyzed the decisions of the General Auditing Office and the Office of the President on 101 workmen compensation cases, 79 of which involved public school teachers and 22 officials and employees of other government offices. The study found lack of consistency and uniformity in the application of principles and precedents in the disposition of cases involving the (1) determination of the service connection of particular illness contracted in line of duty, (2) amount allowed for burial expenses although such amount has been set under executive orders, and (3) reimbursement of expenses occasioned by the hiring of the services of private nurses, therapists, attendants, and physicians and use of private hospitals. The principal defect of Section 699 -- lack of source of funding for the monetary benefits -- was not remedied by RA 1232.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Teachers -- Salaries, pensions, etc. -- Philippines; Workmen's compensation -- Philippines